(untitled) (Revista Lusófona de Educação, 2026)
Abstract The following interview with Professor Ivor Goodson took place during the ACT4WBeing Symposium, an international event that gathered researchers, educators, and practitioners to reflect on education, professional autonomy, and teachers’ well-being in the context of a rapidly digitising and globalised world. Within this symposium, Goodson’s intervention — framed as a live conversation rather than a formal keynote — offered a profoundly humanistic and politically engaged perspective on what it means to educate, research, and live meaningfully today. Ivor F. Goodson is one of the most influential figures in the field of education. A British scholar with a PhD in Philosophy from the University of Sussex, he has taught and conducted research at universities in England, Canada, and the United States, and has been a visiting professor at institutions such as the Max Planck Institute, Sciences Po (Paris), and Stanford University. He was a Professor of International Research at Tallinn University in Estonia and a Senior Research Associate at the Guerrand-Hermès Peace Foundation in Brighton, UK. Previously, he was a Professor of Learning Theory at the University of Brighton’s Education Research Center. Goodson has led major international research projects and authored an extensive and multifaceted body of work on curriculum studies, life history, narrative inquiry, and education policy. Among many distinctions, he received the John Nisbet Fellowship (BERA, 2018), the Michael Huberman Award (AERA), an Honorary Doctorate from the University of Gothenburg, and was elected Fellow of the Academy of Social Sciences (UK).Throughout his career, Goodson has sought to understand how educational policies and curriculum reforms intersect with the lived experiences of teachers and learners. His work defends education as a moral and democratic project, grounded in people’s stories and aspirations rather than in bureaucratic or market imperatives. In this wide-ranging conversation, he reflects on his intellectual trajectory — from curriculum theory to narrative inquiry — and on the ethical, political, and existential challenges that education faces in the twenty-first century.